1998
DOI: 10.1002/(sici)1099-0984(199805/06)12:3<151::aid-per296>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-knowledge and social desirability of personality traits

Abstract: Research into the self-concept has shown that self-knowledge is aected by factors such as trait desirability, trait vagueness, and self-variability. Among these, social desirability appears to play a prominent role. In a multidimensional view of the self, however, several studies indicate that in special conditions people show adequate selfknowledge in speci®c personality dimensions. The present study tests this with respect to extraversion and anxiety predisposition on a sample of 160 late adolescents. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…In line with previous research, we argue that extraverted leaders have higher self compared to other ratings of effectiveness because (a) extraversion positively relates to effectiveness ratings (Judge et al, 2006) and (b) leaders high on an extraversion preference show more socially desirable ratings (Meleddu & Guicciardi, 1998). Thus, leaders with an extraverted preference ought to have higher self-ratings of effectiveness, as these are more socially desirable in leadership settings.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with previous research, we argue that extraverted leaders have higher self compared to other ratings of effectiveness because (a) extraversion positively relates to effectiveness ratings (Judge et al, 2006) and (b) leaders high on an extraversion preference show more socially desirable ratings (Meleddu & Guicciardi, 1998). Thus, leaders with an extraverted preference ought to have higher self-ratings of effectiveness, as these are more socially desirable in leadership settings.…”
Section: Introductionsupporting
confidence: 89%
“…This is mainly explained by the circumstance that the process of creating a particular self-perception would tie attentional and cognitive resources that intuitive persons preferably use for their creative thoughts and open-minded way of thinking. Second, intuitive leaders are less prone to provide socially desired self-ratings and thus should not have inflated self-ratings (Meleddu & Guicciardi, 1998). Third, supervisor, peer, subordinate, and self-ratings of leadership effectiveness are positively linked to a leader’s intuition preference (Vincent, Ward, & Denson, 2015; Johnson et al, 1997; Page, Roberts, & Platt, 2014) whereby the intuition preference has a similarly strong impact on self and other ratings (Brandt & Laiho, 2013; Conway, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The predictive and practical value of this small correlation is negligible. Previous studies in this domain have yielded mixed results (see Gershuny & Sher, 1998;Meleddu & Guicciardi, 1998). In the original Eysenckian model of personality, neuroticism and extraversion should have a zero correlation (Eysenck, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hong and Paunonen (2011) stated that high neuroticism is associated with a broad range of anxiety and mood disorders, whereas low extraversion is associated specifi cally with social phobia, agoraphobia, and depression. Some studies have suggested a negative relation between anxiety and extraversion, albeit weaker than the relation of anxiety and neuroticism (Ferrando, 1994;Meleddu & Guicciardi, 1998). However, other studies have not supported this fi nding (Gershuny & Sher, 1998).…”
mentioning
confidence: 98%
“…In their study of student leaders at the US Naval Academy, Roush and Atwater (1992) also found individuals high on introversion provided performance ratings better aligned with those provided by their subordinates. Meleddu and Guicciardi (1998) found extraverted individuals tend to provide more socially desirable ratings. In the context of 360 performance evaluation, an extraverted individual may be inclined to provide high self-ratings of performance as these may be seen as more socially desirable than lower ratings.…”
Section: Personality Characteristics Potentially Associated With Selfmentioning
confidence: 99%